PERAWATAN BEDAH FLAP PERIODONTAL PADA PERIODONTITIS KRONIS: SEBUAH LAPORAN KASUS - Sri Oktawati; Lilies Anggarwati Astuti (Fakultas Farmasi UMI, 2014)
Chronic periodontitis is an inflammatory disease in periopdontal tissue. Subgingiva specific organisms are to be responsible for this gingiva inflammatory reaction. Gingiva attachment loss would occurred along with alveolar bone destruction, periodontal pocket formation, pathological migration and mobility of teeth. Case: A 48-year-old male was referred to the Departement of Periodontology RGSM Kandea Makassar. On clinical examination, tooth mobility in relation to teeth 31,32,33,34,41,42,43,44 was noticed. Chewing difficulty was reported by the patient. There was no routine control by dentists. Methode: Presurgery examination of teeths 31,32,33,34,41,42,43,44 showed mean pocket depths >5mm, there was gingiva recession and º3 teeth mobility. The patients was managed by an open flap debridement under local anesthesia. All subgingiva deposits were removed using curettes. The tissue was sutured and periodontal pack was put in place. Result: The patient was recalled after 3 weeks for suture removal and reevaluation. His results shows normal gingiva tissue with good tissue attachment. Teeth mobility was decreased by º1. Conclusion: This case report emphasizes the importance of routine dental examination for early intervention of chronic periodontitis.